2021
DOI: 10.1007/s11135-021-01303-7
|View full text |Cite
|
Sign up to set email alerts
|

“Furry tales”: pet ownership’s influence on subjective well-being during Covid-19 times

Abstract: The social distancing required during Covid-19 times tended to make people feel lonelier than usual. Those with pets might, however, have experienced this less, because pets are known for fostering their owners’ subjective well-being. Building on a recently published structural equation model, our study enhances the understanding of subjective well-being by including the construct social distancing during Covid-19 times. In order to answer our research question—How does human-pet relationship need support infl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 88 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…The global experience and diverse aspects included distinguish the Covid-19 pandemic from crises we have known so far (Mihalache & Mihalache 2022 ). Social distancing, despite its impact on peoples’ subjective well-being (Damberg and Frömbling 2021 ), was encouraged by government policies with respect to lockdowns and working from home in many countries (Kumar et al 2021 ). Wang et al ( 2020 ), for example, found that psychological isolation, not physical isolation, adversely affects the emotional relationship of employees to their organizations.…”
Section: Introductionmentioning
confidence: 99%
“…The global experience and diverse aspects included distinguish the Covid-19 pandemic from crises we have known so far (Mihalache & Mihalache 2022 ). Social distancing, despite its impact on peoples’ subjective well-being (Damberg and Frömbling 2021 ), was encouraged by government policies with respect to lockdowns and working from home in many countries (Kumar et al 2021 ). Wang et al ( 2020 ), for example, found that psychological isolation, not physical isolation, adversely affects the emotional relationship of employees to their organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies found no association between animal companionship and depression [85,111,112,116,136,173,185]. One study found animal caregivers had significantly lower levels of distress [100], but three studies found caregivers had significantly greater stress [101,147,151]; in one study [101], this association was found in univariate analysis only, and in another [151] this association was for cat caregivers only. A further six studies found no association between animal companionship and stress [111,112,116,151,173,185].…”
Section: Amount Of Physical Activitymentioning
confidence: 93%
“…Lower isolation: Damberg and Frömbling [100]; Hart et al [114] (dogs only); van der Velpen et al [180] --…”
Section: Isolationmentioning
confidence: 99%
“…In the current period of reduced social interaction because of the coronavirus disease 2019 (COVID- 19), pet ownership may be helpful for improving quality of life. Pet ownership has been reported to have positive benefits, such as reducing psychological distress caused by loneliness [1] and improving health [2]. The pet population in the US is around 157 million, and the number of pet owners has increased in recent years because of increased income [3] and the greater proportion of time spent at home because of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%